A Supraparticle-Based Five-Level-Identification Tag That Switches Information Upon Readout - Miller, Franziska; Wintzheimer, Susanne; Prieschl, Johannes; Strauss, Volker; Mandel, Karl (Advanced Optical Materials, 2020)
Product identification tags are of great importance in a globalized world with increasingly complex trading routes and networks. Beyond currently used coding strategies, such as QR codes, higher data density, flexible application as well as miniaturization and readout indication are longed for in the next generation of security tags. In this work, micron-sized supraparticles (SPs) with encoded information (ID) are produced that not only exhibit multiple initially covert identification levels but are also irreversibly marked as “read” upon readout. To achieve this, lanthanide doped CaF2 nanoparticles are assembled in various quantity-weighted ratios via spray-drying in presence of a broad-spectrum stealth fluorophore (StFl), yielding covert spectrally encoded ID-SPs. Using these as pigments, QR codes, initially dominated by the green fluorescence of the StFl, could be generated. Upon thermal energy input, these particle-based tags irreversibly switch to an activated state revealing not only multiple luminescent colors but also spectral IDs. This strategy provides the next generation of material-based security tags with a high data density and security level that switch information upon readout and can be, therefore, used as seal of quality.
CRIS-Team Scopus Importer:2020-12-25
Keywords: multilevel luminescence identification; rare earth doped nanoparticles; security tags; stealth fluorophores; supraparticles